Implementation of the Student Facilitator and Explaining Model in Learning Skills of Reading Skills in SD - Endang Sri Maruti (Universitas Muhammadiyah Enrekang, 2019)
The purpose of this study was to determine the extent of the implementation of the Student Facilitator Model and Explaining learning model through the media of illustrated story books in improving initial reading skills for first grade students of SDN 01 Taman Kota Madiun 2018/2019 Academic Year. This research includes descriptive qualitative research. By using the phenomenology approach. Data collection techniques are based on data sources, namely RPP, syllabus, observation, interviews. Closed questionnaire. Documentation. The data analysis technique used is the data analysis model of Miles and Huberman. Based on the results of the study, it can be concluded that in the Implementation of the Student Facilitator and Explaining learning model using media illustrated storybooks in Indonesian language lessons are innovative. Based on the results of interviews, documentation, observation and giving questionnaires. Student responses are categorized as good, students' enthusiasm in learning Indonesian language lessons is increasing. Students become fond of learning and student collaboration is also formed in group activities so as to be able to foster a positive attitude towards students in their social interactions.